Effect of Weight Loss in Obese Dogs on Indicators of Renal Function or Disease. (26th December 2012) - Tvarijonaviciute, A.; Ceron, J.J.; Holden, S.L.; Biourge, V.; Morris, P.J.; German, A.J.
Abstract : Background: Obesity is a common medical disorder in dogs, and can predispose to a number of diseases. Human obesity is a risk factor for the development and progression of chronic kidney disease. Objectives: To investigate the possible association of weight loss on plasma and renal biomarkers of kidney health. Animals: Thirty‐seven obese dogs that lost weight were included in the study. Methods: Prospective observational study. Three novel biomarkers of renal functional impairment, disease, or both (homocysteine, cystatin C, and clusterin), in addition to traditional markers of chronic renal failure (serum urea and creatinine, urine specific gravity [USG], urine protein‐creatinine ratio [UPCR], and urine albumin corrected by creatinine [UAC]) before and after weight loss in dogs with naturally occurring obesity were investigated. Results: Urea ( P = .043) and USG ( P = .012) were both greater after weight loss than before loss, whilst UPCR, UAC, and creatinine were less after weight loss ( P = .032, P = .006, and P = .026, respectively). Homocysteine ( P < .001), cystatin C ( P < .001) and clusterin ( P < .001) all decreased upon weight loss. Multiple linear regression analysis revealed associations between percentage weight loss (greater weight loss, more lean tissue loss; r = −0.67, r 2 = 0.45, P < .001) and before‐loss plasma clusterin concentration (greater clusterin, more lean tissue loss; r = 0.48, r 2 = 0.23, P = .003). Conclusion and Clinical Importance: These results suggest possible subclinical alterations in renal function in canine obesity, which improve with weight loss. Further work is required to determine the nature of these alterations and, most notably, the reason for the association between before loss plasma clusterin and subsequent lean tissue loss during weight management.